Quality of reading among equipment for determining water content in corn kernels - Rodrigues, Thais Caroline; Carneiro, Franciele Morlin [UNESP]; Brunini, Rodrigo Garcia; Menezes, Patricia Candida de; Bertonha, Rafael Scabello; Angeli Furlani, Carlos Eduardo [UNESP] (Univ Estadual Londrina, 2020)
Corn productivity in Brazil has been gradually increasing, and adequate storage of produce is a matter of safety; under appropriate storage, the quality of the product is preserved and losses are avoided or minimized. Hence, monitoring temperature and moisture control is essential. The objective of this study was to verify the quality of readings of equipment used to determine the water content of corn seeds according to the sowing times, and to verify the existence of correlations among the equipment. The experiment was conducted at the Research and Extension Teaching Farm (FEPE), which belongs to UNESP/FCAV in Jaboticabal, SP. The experimental design was based on the basic premise of statistical quality control (SQC). Three experimental areas were evaluated with two corn hybrids and with different days after sowing (DAS): Area A (hybrid AS1633PRO2 at 132 DAS), Area B (hybrid AS1555RR2 at 125 DAS), and Area C (hybrid AS1633PRO2 at 150 DAS). To evaluate the water content of the seeds, an expeditious method was employed using two different moisture sensors (Equipment 1 and 2) based on the principle of dielectric measurement (moisture by capacitance). The greenhouse method (Equipment 3) was also tested. The highest reading quality was observed in Equipment 1, and Area C showed less variability and a higher average yield because of the adequate physiological maturation points of the harvest and more appropriate grain water content. Equipment 3 and 1 showed better correlation between the evaluations because the calibration of Equipment 1 had readings close to those of the standard method (Equipment 3).
Keywords: Monitoring; Moisture sensor; Zea mays